Multi Agent Based Audio Steganography - Kartheeswaran, T.; Senthooran, V.; Pemadasa, T.D.D.L. (IEEE, 2015 IEEE International Conference on Computational Intelligence and Computing Research (ICCIC), 2016)
Today’s Information Technology grows rapidly with new technologies and need more security for the data transmissionover the internet. Steganography is one of the solutions to ensurethe data secure over the internet. An audio steganography is amethod to transfer concealed information by changing the coveraudio file without degrading the quality of the original file. Thecover medium before steganography and stego medium aftersteganography should have the same characteristics of a goodsteganographic system. The Agent technology involves distributingthe services with flexible manner. As most of the applications arecreated as services in present computing scenario and data securityalso can be served as a service. Agent-based steganography willimprove the efficiency of the secure steganographic system and itwill be more convenient in terms of flexibility and availability. Inthis research paper, we present a trusted communication platformfor multi-agents that are able to hide the confidential message inthe cover audio stream according to the user request and retrievethe hidden information from the stego audio file. This systemprovides high availability and flexibility in this context and a morefeasible way to trust themessage transmission. This work iscurrently being done and designing part of this work has been donesuccessfully with satisfied results.\
Keywords: Multi Agent System; Software agents; Audio steganography